Genetic polymorphisms of C-type lectin receptors in Behcet’s disease in a Chinese Han population - Yi Yang (Scientific Reports, 2017)
Abstract C-type lectin receptors (CLRs) have been demonstrated to be involved in several autoimmune diseases. The role of CLRs in Behcet’s disease (BD) is unknown and thus was the purpose of this study. A two-stage association study was carried out and a total of 766 BD patients and 1674 healthy controls were recruited. Genotyping of 14 SNPs of 13 genes in CLRs was carried out by iPLEX Gold genotyping or polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) assay. The expression of mannose binding lectin 2 (MBL2) and killer cell lectin like receptor C4 (KLRC4) was measured by Real-time PCR. Significantly increased frequencies of the A allele as well as AA genotype of rs1800450 in MBL2 (Pc = 2.50 × 10−6, OR = 1.494; Pc = 2.24 × 10−6,OR = 2.899; respectively) and TT genotype of rs2617170 in KLRC4 (Pc = 2.53 × 10−6, OR = 1.695) and decreased frequencies of GG genotype of rs1800450 (Pc = 1.56 × 10−3, OR = 0.689) and C allele as well as CC genotype of rs2617170 (Pc = 2.05 × 10−9,OR = 0.664; Pc = 1.20 × 10−5, OR = 0.585; respectively) were observed in BD. Two variants, p.Gly54Asp (rs1800450) and p.Asn104Ser (rs2617170) affect MBL2 and KLRC4 protein stability and expression. Our study demonstrates that the MBL2/rs1800450 and KLRC4/rs2617170 are susceptibility factors for BD in a Chinese Han population.